Safety evaluation of enriched fraction from leaves of Dillenia indica L. in BALB/c mice. (2022) - Singh, Kabrambam D.; Jena, Sarita; Patra, Biswajit; Devi, Thiyam B.; Chawla, Saurabh; Bharali, Rupjyoti; Parida, Ajay; Mukherjee, Pulok K.; Rajashekar, Yallappa
Abstract: The enriched fraction derived from Dillenia indica L. (Dilleniaceae), also known as elephant apple was subjected to acute and sub-acute toxicological study to document its safety issues for use as fumigant. The enriched fractions were orally administered to both sexes of BALB/c mice at doses of 200, 800 and 1600 mg/kg bw for acute toxicity, and 50 and 500 mg/kg bw for 14 days of sub-acute toxicity. Experimental results revealed that there were no signs of adverse toxicity, and mortality, with no significant treatment related effect in the percentage weight gain, daily feed and water intake, and haematological parameters. However, at higher dose in sub-acute toxicity study a patch of mild tubular injuries in kidney of female mice were observed as suggested by histopathological studies and mild abnormalities in levels of serum biochemical parameters. In general, it can be considered that the enriched fraction from D. indica leaves on oral feeding does not show any adverse effect on mice of both sexes. Hence, the highest doses 1600 mg/kg bw (acute) and 500 mg/kg bw (sub-acute) can be used as basal dose for the determination of no-observed-adverse-effect level (NOAEL) of enriched fraction from D. indica to calculate its safety margin. Graphical Abstract: ga1 Highlights: Evaluate the mammalian toxicity of the enriched fraction isolated from the leaves of D. indica on animal model. Enriched active fraction was found to exhibit no adverse effect or mortality on the treated animals. The both test reveals no significant effect on the external appearances, behaviour, body weight and feed and water intake of the treated animals. Hematological studies proved that no significant changes occurred on the treated animals due to oral administration of the enriched fraction. Results reveal that highest doses can be used as basal dose for the determination of no-observed-adverse-effect level of enriched fraction from D. indica to calculate its mammalian safety margin.